2016
DOI: 10.1371/journal.pone.0151829
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids and Dysbiosis in Non-Alcoholic Fatty Liver Disease

Abstract: Background & AimsNon-alcoholic fatty liver disease (NAFLD) is characterized by dysbiosis. The bidirectional effects between intestinal microbiota (IM) and bile acids (BA) suggest that dysbiosis may be accompanied by an altered bile acid (BA) homeostasis, which in turn can contribute to the metabolic dysregulation seen in NAFLD. This study sought to examine BA homeostasis in patients with NAFLD and to relate that with IM data.MethodsThis was a prospective, cross-sectional study of adults with biopsy-confirmed N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
288
2
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(320 citation statements)
references
References 58 publications
21
288
2
9
Order By: Relevance
“…Elevated serum total bile acids in NASH were first reported by Ferslew et al 37. Using approaches that are complementary to ours, Mouzaki et al 17 concluded that bile acid production is elevated in NAFLD livers, based on the findings that faecal total bile acid and faecal primary bile acid levels are elevated in patients with NAFLD, and that serum marker of bile acid synthesis 7-alpha-hydroxy-4-cholesten-3-one is elevated in NAFLD. In support of increased bile acid production, Min et al 38 also observed elevated hepatic expression of CYP7A1 in NAFLD livers.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Elevated serum total bile acids in NASH were first reported by Ferslew et al 37. Using approaches that are complementary to ours, Mouzaki et al 17 concluded that bile acid production is elevated in NAFLD livers, based on the findings that faecal total bile acid and faecal primary bile acid levels are elevated in patients with NAFLD, and that serum marker of bile acid synthesis 7-alpha-hydroxy-4-cholesten-3-one is elevated in NAFLD. In support of increased bile acid production, Min et al 38 also observed elevated hepatic expression of CYP7A1 in NAFLD livers.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, Mouzaki et al 17 examined the gut microbiome composition in NAFLD. Using PCR-based method, they found that patients with NASH exhibited small but significant changes in faecal microbiome, which is in line with altered faecal bile acid composition.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Mouzaki et al. [121] shows that NASH patients had a reduction in the secondary bile acids pool and in fecal levels of Bacteroidetes and Clostridium leptum . However, a direct role of the gut microbiome in controlling FXR-bile acids signaling in NAFLD and NASH development has not been elucidated.…”
Section: Mechanisms For Gut Microbiota Effect On Nafldmentioning
confidence: 97%
“…Lake et al studied the composition of BA’s in the human livers of NAFLD patients and interestingly found a reduced level of CA and glycodeoxycholic acid and an increase in taurocholic acid and taurodeoxycholic acid 54 . A recent study looking at the fecal composition of NAFLD and NASH adults confirmed a higher fecal bile acid level with a predominance of primary bile acids in the stool of NASH patients (NASH>NAFLD), further clarifying the mechanism by which BA’s regulate dysbiosis 55 . To further aseess the interplay Tetri et al in a multicenter randomized trial studied the effect of obeticholic acid (BA derivative that activates FXR) in NASH patients and noted improvement in the histological features of NASH based on the NAFLD activity score on liver biopsies 56 ..…”
Section: Introductionmentioning
confidence: 92%